Cash Benefits for Sickness and Maternity in Selected States of the European Union and Austerity Measures (European Journal of Marketing and Economics, 2025)
The paper introduces the results of the research focused on cash benefits for sickness and maternity in selected Member States of the European Union during the financial crisis and concerns the economic and demographic data. The aim was to determine whether and to what extent the expected austerity measures touched the monitored social area. For the paper we studied the situation from 2009 to 2014, especially in relation to employees and employers. Regarding the methods of the research, the authors gathered the data obtained from the relevant legal, statistical and other printed documents as well as the documents from the website of the European Union, relevant national ministries, social insurance companies, sickness funds and similar institutions. They undertook a legal, economic and demographic data analysis and consequently its comparisons as well as the final evaluation.
Keywords: social security, health insurance, maternity cash benefit, macroeconomic factors